Gender, Family, and Community Correlates of Mental Health in South Asian Americans - Masood, Nausheen (2009)
Nationally representative data from the National Latino and Asian American Study (Alegría et al., 2004) was used to examine both disorder prevalence rates and correlates of distress for the South Asian American subgroup (n = 164). South Asian Americans generally appeared to have lower or comparable rates of lifetime and 12-month mood and anxiety disorders when compared with the overall Asian American sample. A multiple-regression model fitted to predict recent psychological distress, with 12-month diagnosis as a covariate, found gender differences. For women, lack of extended family support was related to higher levels of distress, whereas for men, greater conflict with family culture, and a lower community social position (but higher U.S. social position) predicted higher distress scores. Findings suggest that mental health services consider a broad framework of psychological functioning for South Asian Americans that reflect their gendered, familial, and sociopolitical realities.